The Pear affair - Eagle, Judith (Walker Books, 2022)
In 1969 England, Penelope "Nell" Magnificent attends a boarding school thanks to her self-absorbed parents and pines the loss of her beloved nanny Pear with whom she's kept in contact. During a home visit, Nell's parents mention a trip to Paris, where Pear lives, and Nell begs to go along, using it as a ruse to find Pear, who unexpectedly stopped writing her six months ago. There, she meets a savvy bellboy named Xavier who helps her begin an investigation to find Pear. Nell uncovers a plot of greed and corruption targeting local bakeries and uses her wits and new friends to set things right.